Real-Time Quaking-Induced Conversion Detection of PrPSc in Fecal Samples From Chronic Wasting Disease Infected White-Tailed Deer Using Bank Vole Substrate - Hwang, Soyoun; Greenlee, Justin J.; Nicholson, Eric M. (Frontiers in Veterinary Science, 2021)
Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy (TSE) that is fatal to free-range and captive cervids. CWD has been reported in the United States, Canada, South Korea, Norway, Finland, and Sweden, and the case numbers in both wild and farmed cervids are increasing rapidly. Studies indicate that lateral transmission of cervids likely occurs through the shedding of infectious prions in saliva, feces, urine, and blood into the environment. Therefore, the detection of CWD early in the incubation time is advantageous for disease management. In this study, we adapt real-time quacking-induced conversion (RT-QuIC) assays to detect the seeding activity of CWD prions in feces samples from clinical and preclinical white-tailed deer. By optimizing reaction conditions for temperature as well as the salt and salt concentration, prion seeding activity from both clinical and preclinical animals were detected by RT-QuIC. More specifically, all fecal samples collected from 6 to 30 months post inoculation showed seeding activity under the conditions of study. The combination of a highly sensitive detection tool paired with a sample type that may be collected non-invasively allows a useful tool to support CWD surveillance in wild and captive cervids.